2016
DOI: 10.1136/vr.103425
|View full text |Cite
|
Sign up to set email alerts
|

Immunolabelling of non‐phosphorylated neurofilament indicates damage of spinal cord axons in TSE‐infected goats

Abstract: TRANSMISSIBLE spongiform encephalopathies (TSEs) including bovine spongiform encephalopathy (BSE) are devastating neurodegenerative disorders caused by conversion of the normal cellular prion protein (PrP C) into an abnormal isoform (PrP Sc ; Prusiner, 1982, Chesebro, 2003). Following the discovery of goat BSE cases in the UK and France (Eloit and others 2005, Jeffrey and others 2006, Spiropoulos and others 2011) small ruminants were considered to pose a BSE infection risk/source for cattle, and human beings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In order to establish the progression of hippocampal neurodegeneration throughout aging we used three groups of mice of different ages: adult (3-6 months), old (12-15 months) and aged (more To further evaluate age-associated axonal degeneration in the hippocampus, we studied the expression of two phosphorylated forms of neurofilaments (NFs), the main proteins shaping the axonal cytoskeleton. Most NFs are highly phosphorylated under physiological conditions (Petzold 2005), while increased non-phosphorylated NF (non-pNF) immunoreactivity is associated with inflammation, neurodegenerative diseases and brain injury (Tsunoda & Fujinami 2002;Seehusen & Baumgärtner 2010;Bock et al 2013;Nadeem et al 2016). Interestingly, almost undetectable immunoreactivity of non-pNF was observed in the DG of adult mice, while a progressive increase was evidenced during aging (Fig 1c,d).…”
Section: Resultsmentioning
confidence: 93%
“…In order to establish the progression of hippocampal neurodegeneration throughout aging we used three groups of mice of different ages: adult (3-6 months), old (12-15 months) and aged (more To further evaluate age-associated axonal degeneration in the hippocampus, we studied the expression of two phosphorylated forms of neurofilaments (NFs), the main proteins shaping the axonal cytoskeleton. Most NFs are highly phosphorylated under physiological conditions (Petzold 2005), while increased non-phosphorylated NF (non-pNF) immunoreactivity is associated with inflammation, neurodegenerative diseases and brain injury (Tsunoda & Fujinami 2002;Seehusen & Baumgärtner 2010;Bock et al 2013;Nadeem et al 2016). Interestingly, almost undetectable immunoreactivity of non-pNF was observed in the DG of adult mice, while a progressive increase was evidenced during aging (Fig 1c,d).…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, it can be assumed that their immunoreactivity indicates their axonal localization. These findings indicate that the accumulation of lysosomal storage material might influence axonal transport and neurofilament phosphorylation status [75,76,88,89,103]. A disturbance in the kinesin-mediated transport of dynein could also affect dynein distribution, because dynein transport is also partly dependent on kinesin (direct transport) [104].…”
Section: Discussionmentioning
confidence: 93%
“…NF phosphorylation also controls the association of NFs with kinesin and dynein, and thereby their own axonal transport [100,101]. Thus, alterations in the amount and distribution of β-APP, pNF, nNF, kinesin, and dynein can be used as surrogate markers for axonal damage and disturbed axonal transport [75,76,88,102,103]. Furthermore, the antibodies are restricted to axons only in the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the present study demonstrated that G M1 and NGF supplementation results in an increased expression of pNF and nNF within neuronal processes, which was accompanied by a decrease in the pNF/nNF ratio possibly reflecting changes in the NF phosphorylation status. Normal axons are characterized by highly phosphorylated NFs, whereas damaged axons found in different inflammatory, degenerative and traumatic CNS diseases [114][115][116] and disturbed axonal transport 117,118 contain nNFs. Thus, supplementation of canine DRG neurons with G M1 and NGF might also cause degenerative changes in neuronal processes.…”
mentioning
confidence: 99%